Progress on Molecular Mechanism of Disulfide Death in Gastric Cancer and its Clinical Targeted Treatment Strategy - Yujie Liu (International Journal of Biology and Life Sciences, 2026)
Disulfide death is a newly discovered regulatory cell death mode in 2023, which is driven by the high expression of SLC7A11 and glucose starvation, and is characterized by the collapse of actin skeleton. It shows great potential in the targeted treatment of gastric cancer. This paper systematically reviewed the molecular mechanism of disulfide death, summarized the research progress of disulfide death related genes (DRGs) in the prognosis evaluation, molecular typing and immune microenvironment regulation of gastric cancer, and discussed the targeted treatment strategy based on Glucose Transporter 1 (GLUT) inhibitor, SLC7A11 precise regulation and nano drug delivery system. The results showed that the DRGs related prognostic model can effectively predict the survival of gastric cancer patients, and its low-risk group often presents an "immune fever" phenotype, while the GLUT inhibitor bay-876 has been confirmed in preclinical models to induce disulfide death and inhibit tumor growth. However, the field still faces challenges such as the lack of specific detection markers, functional studies mostly stay in correlation inference and lack of causal mechanism verification. The further research need to analyze the real role of disulfide death in the tumor microenvironment with the help of single-cell and space omics technology, and accelerate the clinical transformation process by carrying out clinical trials with SLC7A11 expression level as a hierarchical marker.